Oxidative stress in relapsing-remitting multiple sclerosis patients - Samaneh Sabouri; Mohsen Foroughipour; Elaheh Emadi; Daryoush Hamidi Alamdari (Reviews in Clinical Medicine, 2023)
Introduction: In multiple sclerosis (MS), oxidative stress (OS) performs a vital role in the neurodegeneration process. Cholesterol and lipids in the myelin sheath supplied by low-density lipoprotein (LDL) are also vital for nerve cells. In OS, lipid peroxidation occurs in LDL. Objective: To investigate the OS biomarker such as prooxidant-antioxidant balance (PAB), malondialdehyde (MDA) and their correlation with LDL and oxidized LDL (Oxi-LDL) in patients with relapsing-remitting MS.Methods: Blood samples from 18 patients with relapsing-remitting MS and 18 healthy subjects were collected to measure the OS biomarkers.Results: In the patients' group in comparison to the control group: PAB, white blood cells (WBC), and neutrophils significantly increased (P<0.05), but there was no difference between the relapsing and remitting phase; MDA significantly increased in the relapsing phase (P=0.013), but marginally significant in remitting (P=0.068). There was no significant difference in LDL and Oxi-LDL between the two groups. Only the lymphocytes were different between the relapse and remission phases. Conclusion: The importance of OS in the process of MS disease was confirmed and a PAB assay can be used for the determination of OS levels.